Congenital abnormalities of the urogenital tract: the clue is in the cord?. (2nd December 2014) - Daoub, Ahmed; Drake, Thomas M
Abstract : Congenital abnormalities of the female urogenital tract are not uncommon, with an estimated incidence of 2–4% across the female population. Within this population, up to 40% will have associated renal tract abnormalities. A previously well 12-year-old girl presented to the emergency department with abdominal pain, vomiting and a palpable pelvic mass. Ultrasound and MR scans were performed. The imaging revealed a didelphys uterus, an obstructed hemivagina and ipsilateral renal agenesis, characteristic of Herlyn-Werner-Wunderlich syndrome. The patient was noted at birth to have a single umbilical artery, which is associated with an increased risk of congenital abnormalities and useful information for the early identification of abnormalities that have implications for renal function and future fertility.